Computation of Nash equilibria in three-personmatrix game - Vakarinienė, Sigutė; Sudžiūtė, Daina (Lietuvos matematikos rinkinys, 2009)
The method for finding Nash equilibrium in three-person matrix game is introduced in this paper. Linear optimization model with binary variables for computation of equilibrium points in three-person matrix game is proposed.